Pedagogical Adaptation Of Olympic Values In The Secondary Education System: A Critical And Analytical Approach - Kostrikova, Kateryna; et al. (European Journal of Social Science Education and Research, 2026)
The principles of Olympism are a trend that has been tested through the use of the multifaceted OlympicFUN program. The article focuses on analyzing the mechanisms of introducing secondary school students to Olympic values, which will help to form key skills in students at the stage of education. The main principles of Olympism are respect, striving to improve one’s skills and solidarity. The program’s methodology is a combination of physical activity and value-based learning using creative reflection practices. This is an opportunity to provide the right conditions for the harmonious development of the child. The study conducted a pedagogical experiment that involved the long-term use of a mixed design of different areas and competencies: social, educational, communicative and cognitive, which were supplemented by qualitative reflections of students. Significant improvements were observed in all areas: social, educational and communicative competencies: the number of students who achieved the formation of values in creativity increased from 19.8% to 68.4%. The feedback allowed us to identify improvements in teamwork and responsibility, as well as in the level of responsibility for morale among the participants. The study proves that Olympic education helps to maintain the quality of core competencies in secondary schools and promote the holistic development of students in line with international priorities.